Utilization of different lignocellulosic hydrolysates as carbon source for electricity generation using novel Shewanella marisflavi BBL25. (20th December 2020) - Gurav, Ranjit; Bhatia, Shashi Kant; Choi, Tae-Rim; Kim, Hyun Joong; Song, Hun-Suk; Park, Sol-Lee; Lee, Sun-Mi; Lee, Hye-Soo; Kim, Sang-Hyoun; Yoon, Jeong-Jun; Yang, Yung-Hun
Abstract: The main approach of the existing study was to harness electrical energy from the waste lignocellulosic biomass mainly comprising glucose and xylose. Novel glucose utilizing Shewanella marisflavi BBL25 was isolated from the microbial communities of the sea-salt harvesting area in Korea. The highest current output density of 1.741 mA/cm 2, and maximum power density of 46.24 mW/cm 2 was achieved in the microbial fuel cell fed with 10 g/L of pure glucose. Nevertheless, the maximum current output density of 6.850 mA/cm 2, 6.661 mA/cm 2 and 6.294 mA/cm 2, and maximum power density of 52.80 mW/cm 2, 40.95 mW/cm 2, and 34.05 mW/cm 2 were attained in the microbial fuel cell fed with barley straw, Miscanthus, and pine hydrolysate with the glucose content adjusted to 10 g/L. Cyclic voltammetry studies revealed the possible role of outer membrane-bound cytochromes and extracellular redox mediators to facilitated electron transfer mechanism. Whereas the metabolic profiling of S. marisflavi BBL25 fueled with plant-based hydrolysates showed the presence of lactate, acetate, pyruvate, formate, succinate, and butyrate as the intermediate metabolites. Interestingly, S. marisflavi BBL25 fed with barley straw hydrolysate showed more elongated cells (3.55–5.90 μm). Graphical abstract: Image 1 Highlights: Novel Shewanella marisflavi BBL25 was isolated from the sea-salt harvesting area. Ferric citrate accelerated electricity production in glucose fed microbial fuel cell. Barley straw-based hydrolysate revealed maximum electricity generation. Cyclic voltammetry studies suggested two different electron transfer pathways. Cost-effective asset to convert biowaste into bioenergy using microbial biocatalyst.